Evaluating an educational device for vocabulary training in schools at Negros Occidental, Philippines - Galang, Sarah Ablagon (Edelweiss Applied Science and Technology, 2025)
Vocabulary is vital to everyone, especially students. Vocabulary training serves as an avenue to help improve students' learning experiences. The paper aimed to design and evaluate an educational device to enhance learners' vocabulary. The study employed a descriptive-evaluative research design utilizing user engagement, educational effectiveness, user interface, motivational factors, and overall satisfaction. The device was introduced to different schools, including public and private schools, and State Universities and Colleges (SUCs) with four hundred thirty-nine (439) respondents. Data analysis involved mean and standard deviation, employing respondents' feedback on the acceptability of the device. The framework used input, process, output, and outcome (IPOO). The findings revealed that using the device, overall ratings ranged from "Very Good" to "Excellent," with State Universities and Public Schools consistently yielding the highest scores across all dimensions and variables. The device also rated "Very Engaging," "Very Effective," and "Very User-Friendly" in most contexts, and students' vocabulary improved. The educational device proves to be a valuable tool for vocabulary development, adaptable across educational stages from elementary to university. These results support its broader implementation and encourage teachers, especially in integrating gamified learning into regular instruction. Thus, students learned many unfamiliar words.